PENILAIAN DAN EVALUASI PENDIDIKAN DI SEKOLAH DASAR - Nurhidayani; Nirmayani Tiala; Riswanto; Rafidah Mutmainnah; Idawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Assessment and evaluation are essential components in the educational process, particularly at the elementary school level, which serves as the foundation for students’ academic, social, and character development. Assessment is not merely used to measure learning outcomes, but also to monitor learning processes and support students’ overall growth. This article aims to examine the concepts, principles, forms, and procedures of assessment and educational evaluation in elementary schools, as well as their role in improving learning quality. This study employs a library research method by analyzing books, scientific journal articles, educational policy documents, and relevant regulations related to assessment and evaluation. The findings indicate that effective assessment must be objective, valid, reliable, transparent, comprehensive, and fair, covering attitudes, knowledge, and skills through authentic assessment. Educational evaluation conducted systematically—from planning to follow-up—plays a strategic role in enhancing learning effectiveness, identifying students’ learning difficulties, and supporting continuous improvement in elementary education